Does repetitive physical loading inhibit radial growth in female gymnasts? - Caine, D.; Howe, W.; Ross, W.; Bergman, G. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: Stress-related injuries to the distal radius have been noted in female gymnasts with potential for resultant premature closure and abnormal growth at this site. The purpose of this study was comprehensively to review and critically to appraise the available literature to examine the evidence related to this question: does repetitive physical loading inhibit growth of the radius in female gymnasts? DATA SOURCES: MEDLINE and SPORT Discuss were searched from 1975 to the present by using "gymnast" in combination with injury, growth plate, epiphyseal, and ulnar variance. Additional references were retrieved from the bibliographies of the retrieved articles. STUDY SELECTION: All descriptive and analytic studies that included data related to stress-related injuries affecting the distal radius of competitive female gymnasts were included. Conclusions regarding the effects of gymnastics training on radial growth of female gymnasts were limited to data from case reports, clinical series, cross-sectional studies, and descriptive cohort studies. Data from relevant experimental animal studies also were included. DATA EXTRACTION AND SYNTHESIS: In reviewing the literature, particular attention was paid to the relative strengths of the different study designs. From these data, information associated with growth inhibition at the distal radius was examined. MAIN RESULTS: The descriptive research reviewed included clinical, cross-sectional, and cohort studies that establish the existence of stress-related injuries affecting one or more constituent parts of the epiphyseal-physeal-metaphyseal (EPM) complex of the distal radius, symptomatic ulna-radial-length difference (URLD), and distal radius physeal arrest among female gymnasts. Five cross-sectional studies showed radiographic abnormalities consistent with distal radius physeal-stress reaction in 10-85% of gymnasts studied. Two cross-sectional studies indicated "abnormal" positive URLD in 8-20% of wrists radiographed. Four cross-sectional studies showed significant correlations between training intensity and URLD, suggesting a dose-response relation. Three cross-sectional studies indicate greater URLD in gymnasts compared with nongymnasts. Radiographic evidence of distal radius physeal arrest involving physically immature female gymnasts is presented in four studies (two clinical series, one cross-sectional, and one descriptive cohort). In animal studies, prolonged physical training has also been shown to inhibit or stop growth in weight-bearing long bones. However, there were no rigorous studies (i.e., randomized control trials or analytic cohorts) examining the question. CONCLUSION: The results of this critical review of the scientific literature support the plausibility of stress-related distal radius physeal arrest with secondary URLD. However, the strength of evidence is inadequate to be conclusive.